Turning building renovation measures into energy saving opportunities. Issue 2 (11th May 2015) - Gohardani, Navid; Af Klintberg, Tord; Björk, Folke
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to promote energy saving measures concurrent with major planned renovation/refurbishment in residential buildings. Design/methodology/approach – The methodology comprises of case studies, in which the influence of various factors is identified on the overall decision making related to building renovation/refurbishment. Findings – The employed operational decision support process enables energy saving opportunities for residential buildings in conjunction with planned major renovations/refurbishments. Research limitations/implications – The research scope is confined to residential buildings in Sweden and cooperatives with tenants as the owners and governors. Practical implications – A novel approach to synergistic energy saving and renovation in residential buildings is exhibited. Social implications – The paper presents an altered viewpoint of energy renovation means for residential buildings in the built environment. Originality/value – The paper presents a novel approach for building owners to renovate a building in terms of improved performance, energy efficiency and indoor comfort in combination with planned renovations/refurbishments.